Educator Perceptions of Soft Skill Development: An Examination within the Malaysian Public Higher Education Sector - Meor Osman, W. S.; Girardi, A.; Paull, M. (Common Ground Publishing LLC, 2011)
Recognition of the importance of soft skills in today's workforce has gained increasing momentum, with educators and industry bodies identifying that generic skills are vitally important to business success. Despite this acknowledgement, a survey of the current literature highlights that many higher education institutions (HEIs) maintain a stronger emphasis on subject-specific knowledge and skill development when compared to soft skills. A number of factors have been shown to influence the development of soft skills including demographic markers, professional body/accreditation requirements and educator personal expectations or views. In this study, the focus is on those educator perceptions which influence the teaching and learning of soft skills. The study is set in Malaysia, where the Ministry of Higher Education (MOHE) has formally acknowledged the importance of seven skills. Semi-structured interviews were used to examine the views of 25 educators from five Malaysian Public HEIs. Findings from the interview showed that educator beliefs and their personal expectations or views influenced their emphasis on the teaching and learning of soft skills. The findings of the study have implications for educators, HEIs and policy makers, and for future research into the effectiveness, roles and responsibilities of HEIs in this important area.